2021
DOI: 10.1136/thoraxjnl-2020-216223
|View full text |Cite
|
Sign up to set email alerts
|

Chronic airflow obstruction and ambient particulate air pollution

Abstract: Smoking is the most well-established cause of chronic airflow obstruction (CAO) but particulate air pollution and poverty have also been implicated. We regressed sex-specific prevalence of CAO from 41 Burden of Obstructive Lung Disease study sites against smoking prevalence from the same study, the gross national income per capita and the local annual mean level of ambient particulate matter (PM2.5) using negative binomial regression. The prevalence of CAO was not independently associated with PM2.5 but was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Besides, patients with moderate to severe COVID-19 disease are more likely to develop multi-organ disease, e.g. myocardial injury, thromboembolic complications, liver failure, and pneumothorax [ 6 10 ]. Comparably, patients after Acute Respiratory Distress Syndrome (ARDS) suffer from long-term physical problems and lung function deterioration [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, patients with moderate to severe COVID-19 disease are more likely to develop multi-organ disease, e.g. myocardial injury, thromboembolic complications, liver failure, and pneumothorax [ 6 10 ]. Comparably, patients after Acute Respiratory Distress Syndrome (ARDS) suffer from long-term physical problems and lung function deterioration [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biomass fuel use for cooking and heating was found not to be a risk factor for post-bronchodilator SAO [ 13 ] in keeping with previous research on CAO [ 50 ], although available data are limited. However, in a single study, exposure to high annual levels of PM2.5 was associated with increased risk of post-bronchodilator SAO [ 13 ], contradicting previous research in populations with CAO [ 51 ]. In support of an association between SAO, smoking and PM2.5, the five included cohort studies reported a greater decline in FEF 25–75 among current smokers, compared to never or former smokers [ 30 ], and a lesser decline in FEF 25–75 in individuals exposed to lower levels of air particulates.…”
Section: Discussionmentioning
confidence: 92%
“…In patients with stable COPD continuous smoking cessation improves, over time, respiratory symptoms and decreases the accelerated decline in forced expiratory volume in one second (FEV1) and mortality 55 and improves the clinical efficacy of inhaled glucocorticoids 56,57 , although it does not completely remove chronic inflammation of their lower airways 57,58 . To help current smokers with stable COPD to stop smoking, supportive drug therapies are also available 59 . However, double-blind randomized placebo-controlled clinical trials on supportive drug therapies for smoking cessation conducted in stable COPD patients, have shown unsatisfactory long-term results 1,59 and therefore this important public health problem requires greater research efforts 60 .…”
Section: Management Of Stable Copd According To the Aetiology Of The ...mentioning
confidence: 99%